NFAT transcription factor regulation by urocortin II in cardiac myocytes and heart failure - Walther, Stefanie (American Physiological Society, 2014)
Urocortin II (UcnII), a cardioactive peptide with beneficial effects in normal and failing hearts, is also arrhythmogenic and prohypertrophic. We demonstrated that cardiac effects are mediated by a phosphatidylinositol-3 kinase (PI3K)/Akt kinase (Akt)/endothelial nitric oxide synthase (eNOS)/nitric oxide (NO) signaling pathways. Nuclear factor of activated T-cells (NFAT) transcription factors play a key role in the regulation of gene expression in cardiac development, maintenance of an adult differentiated cardiac phenotype, and remodeling processes in cardiac hypertrophy and heart failure (HF). We tested the hypothesis that UcnII differentially regulates NFAT activity in cardiac myocytes from both normal and failing hearts through the PI3K/Akt/eNOS/NO pathway. Isoforms NFATc1 and NFATc3 revealed different basal subcellular distribution in normal and HF rabbit ventricular myocytes with a nuclear NFATc1 and a cytosolic localization of NFATc3. However, in HF, the nuclear localization of NFATc1 was less pronounced, whereas the nuclear occupancy of NFATc3 was increased. In normal myocytes, UcnII induced nuclear export of NFATc1 and attenuated NFAT-dependent transcriptional activity but did not affect the distribution of NFATc3. In HF UcnII facilitated nuclear export of both isoforms and reduced transcriptional activity. NFAT regulation was mediated by a PI3K/Akt/eNOS/NO signaling cascade that converged on the activation of several kinases, including glycogen synthase kinase-3β (GSK3β), c-Jun NH(2)-terminal kinase (JNK), p38 mitogen-activated kinase (p38), and PKG, resulting in phosphorylation, deactivation, and nuclear export of NFAT. In conclusion, while NFATc1 and NFATc3 reveal distinct subcellular distribution patterns, both are regulated by the UcnII-PI3K/Akt/eNOS/NO pathway that converges on the activation of NFAT kinases and NFAT inactivation. The data reconcile cardioprotective and prohypertrophic UcnII effects mediated by different NFAT isoforms.